Ion hydration and association in aqueous potassium tetrahydroxyborate solutions. Issue 6 (29th January 2020) - Zhu, Fayan; Yamaguchi, Toshio; Yoshida, Koji; Zhang, Wenqian; Liu, Hongyan; Zhou, Yongquan; Fang, Chunhui
Abstract : The overlapping peaks are clearly investigated in the form of pair distribution functions using the EPSR program. Abstract : Potassium tetrahydroxyborate solution is a significant material in the borate solution family, but there is limited knowledge about hydration structures and interactions of K +, [B(OH)4 − ], and water. In this study, the X-ray diffraction measurements of potassium tetrahydroxyborate solutions have been made. The experimental structure factors are subjected to Empirical Potential Structure Refinement (EPSR) modeling to reveal the details of ion hydration and association in the aqueous solutions. This study shows that the O(W)–O(W) distance of water in the studied solutions ranges from 2.82 to 2.76 Å with a coordination number that ranges from 4.7 ± 1.4 to 3.1 ± 1.3 when the value of the water–salt molar ratio (WSR) is decreased from 30 to 6. The addition of ions slightly affects the tetrahedral structure of water even when the concentration of ions is high. The first hydration distance of K + remained at ∼2.67 Å, whereas the value of the coordination number (CN) decreased from 5.4 ± 1.3 to 3.9 ± 1.5 when the concentration of the borate solution was increased. The hydration ability of K + was weak and almost did not have a fixed local hydration structure. The pair distribution function (PDF) of g B–O(W) ( r ) shows that [B(OH)4 − ] has a broad hydration distance from 2.9 to 5.4 Å because of the complex interactive relationship between K +, [B(OH)4 − ] and water. There is a competitive hydration between K + and [B(OH)4 − ]. Both the X-ray diffraction and DFT-based calculations confirm that the main species is monodentate contact ion pairs when WSR = 30, bidentate contact ion pairs when WSR = 14, and triple contact ion pairs when WSR = 6. These results will provide a new understanding about potassium tetrahydroxyborate solution.